Acute lower respiratory infections: real-world evidence of antibiotic prescription pattern and costs from a large administrative Italian database. (25th January 2022) - Calabria, Silvia; Dondi, Letizia; Ronconi, Giulia; Piccinni, Carlo; Pedrini, Antonella; Esposito, Immacolata; Addesi, Alice; Maggioni, Aldo Pietro; Martini, Nello
Abstract: Objective: This observational retrospective analysis aimed to describe antibiotic prescription pattern in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) and community-acquired pneumonia (CAP) and their costs, from the Italian National Health Service perspective. Methods: From the ReS database, a cross-linkage of Italian healthcare administrative databases through a unique anonymous code allowed to select subjects aged ≥12 years, supplied with at least an antibacterial for systemic use (ATC code: J01) from 01/01/2017 to 12/31/2017 and evaluable until the end of 2018. Prescriptions of different antibiotics on the same date were excluded. The prescription pattern was assessed for patients with an AECOPD (aged ≥50) or a CAP event (aged ≥12) in 2017. A 30-day cost analysis after the antibacterial supply and according to absence/presence (15 days before/after the supply) of AECOPD/CAP hospitalization was performed. Results: In 2017, among patients aged ≥12 ( 5 million), 1, 845, 268 were supplied with ≥1 antibacterial (37.2%). Antibacterial prescriptions potentially related to AECOPD were 39, 940 and 4, 059 to CAP: quinolones were the most prescribed (37.2% and 39.0%, respectively), followed by third-generation cephalosporins (25.5%; 27.5%), penicillins (15.4%; 14.9%), and macrolides (14.4%; 11.3%); the 30-day mean cost was €709 and €2, 889. An association AECOPD/CAP-antibacterial supply costed more when the hospitalization occurred 15 days after the antibiotic supply (€5, 006 and €4, 966, respectively). Conclusions: Findings confirmed the very high use of antimicrobials in Italy and highlighted the urgent need of improving current prescribing practices and developing new molecules, to stop the incessant spread of antimicrobial resistance and related socioeconomic impacts. Lay Summary: Through this retrospective observational analysis of the Fondazione ReS (Ricerca e Salute) database, collecting Italian healthcare administrative data, antibacterial for systemic use supplied to subjects aged ≥12 years in 2017 were identified as potentially prescribed to treat an acute exacerbation of chronic obstructive pulmonary disease (AECOPD) (39, 940; 91%) or an event of community-acquired pneumonia (CAP) (4, 059; 9%). The most used antimicrobials were quinolones (37.2% and 39.0% of antibiotics related to AECOPD and CAP, respectively), third-generation cephalosporins (25.5%; 27.5%), penicillins (15.4%; 14.9%), and macrolides (14.4%; 11.3%). Costs of each patient supplied with the antibacterial to treat AECOPD/CAP were assessed within 30 days after the antibacterial supply. Overall, the integrated cost of the association AECOPD/CAP-antibacterial was higher if the patient was hospitalized due to AECOPD/CAP before the antibacterial supply (€5, 006/€4, 966, respectively). The integrated expenditure of a patient treated for AECOPD not requiring hospitalization was €647. Findings showed a substantial antimicrobial use in Italy for the 2 acute lower respiratory tract infections, highlightening the need of improving the current prescribing practice or developing new molecules. This study also provided healthcare integrated costs of these associations as a proxy of the complexity and frailty of patients experiencing an AECOPD/CAP event.